Filhos de professores = profissão professor? - Machado, Ana Paula Oliveira (2004)
This research brings out the questions related to personal life history, as well as its relation with the problems of the research filed of teacher formation. As a special student of the Post Graduation Program in Education at UFSM, the chance of telling my life experiences since pupil until my graduation as teacher was given to me. When reflecting on my proper life history, many questions had appeared that led to the justification and the importance of such research: I come from a family of teachers (grandmothers, uncle-grandmothers, aunts, cousins and parents...) and I ask to myself: which was the influence of the family in my choice in being a teacher? What makes children of teachers to become teachers? Observing the depreciation of the professor and the profanation of the teaching, the process of teaching identification and the problematic formation courses, as well as the familiar experience, all this leads to the following question: what makes the children of teachers to opt for the profession of their parents? How the parents exert (if they do) any influence in the professional options of their children? Which is the imaginary setting that the children possess, or that the parents transmit to their children about being a teacher nowadays? Which profession do adolescent children of teachers want to opt? And what for? In this sense, aiming at to know the family influence in the choice for courses of formation of teachers and the processes of the professional option of children of teachers, through life histories of parents and children and, more specifically, when investigating the formation process of teacher parents, as well as its influences in the professional education of their children; to understand the social imaginary of the choice of the adolescent children of teachers, trying to know their conceptions of being a teacher nowadays? This study searches the contributions of authors who argue the subject of the theory of Social Imaginary, the formation of teachers and their process of identification about the family and the teaching memory. The data collection was carried out with two families from the town of Santa Maria/RS: in one of them, the daughter followed the teaching profession; in the other one, the daughter did not opt to follow the profession of her parents. Observing the wealthy report of the collaborators of this investigation it is possible to infer that the family has positive or negative influence in the professional choices (in what it is wanted or not). Thus, some of them become teachers to improve the family income or, because they find themselves in the area in which they act, even without never having thought about being a teacher; but after already being acting, they finish becoming teachers and after that, they start to fill an emptiness, thus giving a direction to their existence.